Adam Smith in Toulouse and Occitania : the unknown years - Alcouffe, Alain 1945- (Palgrave Macmillan, 2020)
This book provides substantial background on what Adam Smith did during his stay in Toulouse and the Languedoc region of France during the 18th century. This is a crucial period in Smith's life for at least two reasons: i) it is during this time that Smith began to work on The Wealth of Nations; and ii) it is generally understood that although some of his ideas about political economy were already formed before his trip, his encounters with many French political economists during his time in France helped him to further develop them. As such, this book provides a rich resource to further understanding Smith's world, his travel experiences and the people he met during this time and situates these within the broader context of Smith's life as a whole, and within the British aristocracy.